2021
DOI: 10.3390/molecules26040913
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Analyses of Cotyledon and Plumule Showing the Potential Domestic Selection in Lotus Breeding

Abstract: Lotus (Nelumbo nucifera) seeds are widely consumed as functional food or herbal medicine, of which cotyledon (CL) is the main edible part, and lotus plumule (LP) is commonly utilized in traditional Chinese medicine. However, few studies have been conducted to investigate the chemical components of CL and LP in dry lotus seeds, not to mention the comparison between wild and domesticated varieties. In this study, a widely targeted metabolomics approach based on Ultra Performance Liquid Chromatography-electrospra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Lotus has been cultivated in Asia for over 7000 years and domesticated into three different subgroups: FL, RL, and SL, based on the specific characteristics of flower, rhizome, and seed, respectively ( Ming et al., 2013 ). Although many studies have been conducted to illuminate causal factors of different agronomic traits ( Huang et al., 2018 ; Li et al., 2020 ; Liu et al., 2020 ; Qi et al., 2021 ), few works were done to clarify the dispensable genome in each subgroup. A single reference genome was inefficient in identifying whole genetic variations within one species, limiting the genetic improvement in crops ( Tao et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lotus has been cultivated in Asia for over 7000 years and domesticated into three different subgroups: FL, RL, and SL, based on the specific characteristics of flower, rhizome, and seed, respectively ( Ming et al., 2013 ). Although many studies have been conducted to illuminate causal factors of different agronomic traits ( Huang et al., 2018 ; Li et al., 2020 ; Liu et al., 2020 ; Qi et al., 2021 ), few works were done to clarify the dispensable genome in each subgroup. A single reference genome was inefficient in identifying whole genetic variations within one species, limiting the genetic improvement in crops ( Tao et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Starch branching enzyme (SBE) genes are key regulatory genes during starch synthesis, and NnSBEI and NnSBEIII were identified as related to the chain length of amylopectin in lotus [65]. In addition, comparative metabolomics between wild germplasm "CA" and domesticated cultivar "JX-17" indicated that the seed yield and the content of metabolites showed tradeoffs [66]. For nutritional and medicinal values of lotus seed, the metabolomics-assisted strategy might be applied in lotus breeding in the future [67].…”
Section: Identification Of Genes With Potential Application In Lotus ...mentioning
confidence: 99%